2018
DOI: 10.1167/iovs.18-23813
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability of Three-Dimensional Macular Parameters for Glaucoma Using Optical Coherence Tomography Volume Scans

Abstract: PurposeTo compare the diagnostic capability of three-dimensional (3D) macular parameters against traditional two-dimensional (2D) retinal nerve fiber layer (RNFL) thickness using spectral domain optical coherence tomography. To determine if manual correction and interpolation of B-scans improve the ability of 3D macular parameters to diagnose glaucoma.MethodsA total of 101 open angle glaucoma patients (29 with early glaucoma) and 57 healthy subjects had peripapillary 2D RNFL thickness and 3D macular volume sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Table 1 summarizes spectral-domain (SD) commercially available OCT protocols used to analyze macular ganglion cells. 18,[38][39][40][41][42][43][44] The RTVue-100 software (Optovue, Inc., Fremont, CA) acquires 26,000 A-scans per second with an axial resolution of 5 μm in the tissue. 18,38 The GCC is defined as the sum of RNFL, GCL and IPL thickness measured from the inner limiting membrane to the IPL boundaries ( Figure 1).…”
Section: Macular Ganglion Cell Complex Imaging Topographic Distributimentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes spectral-domain (SD) commercially available OCT protocols used to analyze macular ganglion cells. 18,[38][39][40][41][42][43][44] The RTVue-100 software (Optovue, Inc., Fremont, CA) acquires 26,000 A-scans per second with an axial resolution of 5 μm in the tissue. 18,38 The GCC is defined as the sum of RNFL, GCL and IPL thickness measured from the inner limiting membrane to the IPL boundaries ( Figure 1).…”
Section: Macular Ganglion Cell Complex Imaging Topographic Distributimentioning
confidence: 99%
“…54 The presence of SD-OCT artifacts caused by segmentation or acquisition errors can limit the diagnostic ability of GCC analysis, and the segmentation artifacts were considered the most frequent in both healthy and glaucoma patients. 39 Other factors might influence the interpretation of GCC results; in particular, the epiretinal membrane can cause errors in segmentation, but also retinal disorders and optic neuropathies can alter the GCC thickness. However, these conditions typically do not exhibit specific patterns of GCC damage, but it is important to consider other potential confounding influencing factors when interpreting GCC maps in glaucomatous eyes.…”
Section: Diagnostic Accuracy Reproducibility and Clinical Validationmentioning
confidence: 99%
“…Three-dimensional scans may be less susceptible to artifacts than 2D scans because they carry a higher density of information (e.g., 193 B-scans in a raster pattern vs. a single circular B-scan). 29 , 31 If one B-scan contains an artifact, neighboring B-scans can provide sufficient information to correct the affected frame or B-scan. In contrast, the accuracy of 2D peripapillary RNFL thickness relies on a single frame, so there are no neighboring scans to correct for any bad data.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 30 , 42 Studies of high-density peripapillary RNFL volume scans and high-density macular volume scans have likewise found that average group RNFL volume and average group macular volume values were similar before and after correction of artifacts and subsequent automated interpolation. 21 , 31 On the other hand, 2D peripapillary RNFL thickness and 2D neuroretinal rim measurements generated along a flat reference plane (e.g., cup-to-disc ratio and rim area) on average undergo significant changes after correction of segmentation errors. 17 , 23 , 24 , 40 , 43 The need to manually fix errors or repeat scans in the clinic requires extra time and attention, and parameters derived from 3D volume scans appear to reduce this need.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that harnessing the additional structural information from 3D OCT data provides at least the same, or better, diagnostic capabilities as RNFL thickness measurements in 2D, but with fewer artifacts. 14 21 In particular, two candidate 3D neuroretinal rim parameters, namely (1) the Bruch’s membrane opening-minimum rim width (BMO-MRW) and (2) the minimum distance band (MDB) thickness, have been identified to better delineate the ONH geometry through OCT-derived features. 14 , 17 , 20 , 22 The BMO-MRW is defined by the minimum distance between the BMO and the inner limiting membrane (cup) surface and is calculated using a relatively low-density radial scan protocol.…”
mentioning
confidence: 99%